The challenges of research nursing in an outbreak setting. Issue 3 (September 2016) - Ferguson, Susie
As a respiratory research nurse, my day-to-day work involves running both observational studies and clinical trials of investigational products for patients with chronic obstructive pulmonary disease. Towards the end of 2014, I responded to an advert from the Centre for Tropical Medicine and Global Health at Oxford University, who were looking for research nurses to work on a fast-tracked clinical trials programme in West Africa, made possible by a grant from the Wellcome Trust. As part of the International Severe Acute Respiratory and Emerging Infections Consortium (ISARIC), the team in Oxford, along with other partners, was to test the effectiveness of promising drugs for the treatment of Ebola virus disease. Based on available data, promising drugs were shortlisted by the World Health Organization (WHO) who facilitated their availability and had taken the decision that in such circumstances it was ethical to fast track the trial of drugs still at a relatively early stage of testing. The challenges of research nursing in an outbreak setting http://ow.ly/jOFu301NzRh